Double hit lymphoma: the MD Anderson Cancer Center clinical experience. (18th June 2014) - Oki, Yasuhiro; Noorani, Mansoor; Lin, Pei; Davis, Richard E.; Neelapu, Sattva S.; Ma, Long; Ahmed, Mohamed; Rodriguez, Maria Alma; Hagemeister, Fredrick B.; Fowler, Nathan; Wang, Michael; Fanale, Michelle A.; et al.
Summary We report our experience with 129 cases of double hit lymphoma (DHL), defined as B‐cell lymphoma with translocations and/or extra signals involving MYC plus BCL2 and/or BCL6. All cases were reviewed for histopathological classification. Median age was 62 years (range, 18–85), 84% of patients had advanced‐stage disease, and 87% had an International Prognostic Index score ≥2. Fourteen patients (11%) had a history of low‐grade follicular lymphoma. MYC translocation was present in 81%, and extra signals of MYC in 25% of patients. IGH‐BCL2 translocation was present in 84% and extra signals of BCL2 in 12% of patients. Two‐year event‐free survival (EFS) rates in all patients and patients who received R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone), R‐EPOCH (rituximab, etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin), and R‐HyperCVAD/MA (rituximab, hyperfractionated cyclophosphamide, vincristine, doxorubicin, dexamethasone, alternating with cytarabine plus methotrexate) were 33%, 25%, 67% and 32%, respectively. In patients achieving complete response with initial therapy (n = 71), 2‐year EFS rates in patients who did (n = 23) or did not (n = 48) receive frontline stem cell transplantation were 68% and 53%, respectively (P = 0·155). The cumulative incidence of central nervous system involvement was 13% at 3 years. Multivariate analysis identified performance status ≥2 and bone marrow involvement as independent adverse prognostic factors for EFS and OS. Further research is needed to identify predictive and/or targetable biological markers and novel therapeutic approaches for DHL patients.